Are geographers religiously unmusical? Positionalities in geographical research on religion - Henkel, Reinhard (ERDKUNDE, 2011)
Although there are indications that more geographers are taking up religion as an area of interest, geography of religion still is a subfield that is not very well developed. In particular, many new cultural geographers seem to shy away from including religion into their research as markers of identity alongside race, class and gender. The article investigates the reasons for this attitude, which has a long history and is connected with the (perceived) contrast between science and religion and the secularization thesis. For a long time, this was the generally accepted explanation for the decline of the significance of religion in Western societies, but recently this has been seriously questioned in its validity. In addition, the paper handles the question as to whether methodological agnosticism is the (only) adequate approach in doing research on religion from a social or cultural science view. If research is taken seriously, all researchers are inevitably confronted with their own biographies; with contingencies of cultural imprints and with influences of certain (a)religious milieux. So it is essential that they are aware of this and do not ignore it when researching. Being a believer certainly is not a disadvantage in doing research on religion but can be an advantage, just as it is an advantage or even a necessity for a musicologist to be able to read and practise music.